Takayasu arteritis in pregnancy: a case report, and clinical lessons learnt - Sakhare, Anil P.; Bhandari, Tejas P.; Solanke, Jaydeep R.; Ghante, Rahul J. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
A case report of known case of Takayasu arteritis (known to the woman in case report) in a primigravida, but unrevealed to the obstetrician till advanced stage of pregnancy is reported. The authors share the lessons learnt by them from this case which would improve diagnosis, evaluation and management of pregnancy hypertension. A brief account on clinical manifestations and diagnosis of Takayasu arteritis is also included.